"Willing victims" : a study of Zimbabwean migrant workers in the citrus industry of the Sundays River Valley, Eastern Cape - Maisiri, Brandon James (Rhodes University, Faculty of Humanities, Department of Sociology)
The citrus fruit industry is a large, lucrative industry on the global market. South Africa's citrus fruit industry competes globally and is firmly intergraded into the citrus global value chain (GVC). Sunday River's Valley (SRV) in the Eastern Cape is a powerhouse citrus producer in South Africa. This dissertation interrogates the impact of the citrus value chain on Zimbabwean unskilled immigrant farmworkers in the SRV, positioned at the bottom of the value chain. Mainstream global chain literature, which adopts a neo-liberal approach to development, assumes that businesses in the global south stand to benefit from integrating into global chains. This line of thinking also assumes that, by virtue of the suppliers' experiencing economic upgrading, farm owners' employees may experience social upgrading. The idea of social upgrading stems from the International Labour Organisation's Decent Work Agenda, which promotes workers' rights and conditions globally. In the agricultural sector, there is a growing trend of producers (in the global south) employing undocumented immigrant farmworkers. Free market economists perceive these immigrants' employment in the agricultural value chain as a progressive step for immigrants to step out of poverty. This study employs a qualitative research method to analyse social upgrading for immigrant workers in the citrus GVC. This is done by examining the selected workers' working and living conditions against the key pillars of the Decent Work Agenda. Using the critical GVC framework and a Marxist orientation, this study seeks to show that the use of migrant (especially undocumented) labour in the agricultural value chains is not empowering immigrants in the global south but is essentially a strategy of securing cheap and docile labour for profit maximization. While this can be said for local South African workers as well, the migrant workforce is peculiar as their fragile citizenship in South Africa makes them a less resistant labour force to farm owners labour law violations. This study's findings validate this contention, as they show that immigrants employed in the citrus industry in the Eastern Cape are subjected to several Decent Work deficits. The findings also show that these immigrants have no access to mechanisms of empowerment and are barely surviving from their earnings.
Keywords: Migrant agricultural laborers -- South Africa Sundays River (Eastern Cape); Foreign workers, Zimbabwean -- South Africa Sundays River (Eastern Cape); Citrus fruit industry -- South Africa Sundays River (Eastern Cape); Job creation -- South Africa Sundays River (Eastern Cape); Work environment -- South Africa Sundays River (Eastern Cape); Agricultural wages Social aspects -- South Africa Sundays River (Eastern Cape); Marginality, Social -- South Africa Sundays River (Eastern Cape); Migrant agricultural laborers Legal status, laws, etc -- South Africa; Global Value Chains; International Labour Organisation's Decent Work Agenda